Rare Neurologic Disease-Associated Mutations of AIMP1 Are Related with Inhibitory Neuronal Differentiation Which Is Reversed by Ibuprofen - Yu Takeuchi; Marina Tanaka; Nanako Okura; Yasuyuki Fukui; Ko Noguchi; Yoshihiro Hayashi; Tomohiro Torii; Hiroaki Ooizumi; Katsuya Ohbuchi; Kazushige Mizoguchi; Yuki Miyamoto; Junji Yamauchi (Medicines, 2020)
Background: Hypomyelinating leukodystrophy 3 (HLD3), previously characterized as a congenital diseases associated with oligodendrocyte myelination, is increasingly regarded as primarily affecting neuronal cells. Methods: We used N1E-115 cells as the neuronal cell model to investigate whether HLD3-associated mutant proteins of cytoplasmic aminoacyl-tRNA synthase complex-interacting multifunctional protein 1 (AIMP1) aggregate in organelles and affect neuronal differentiation. Results: 292CA frame-shift type mutant proteins harboring a two-base (CA) deletion at the 292th nucleotide are mainly localized in the lysosome where they form aggregates. Similar results are observed in mutant proteins harboring the Gln39-to-Ter (Q39X) mutation. Interestingly, the frame-shift mutant-specific peptide specifically interacts with actin to block actin fiber formation. The presence of actin with 292CA mutant proteins, but not with wild type or Q39X ones, in the lysosome is detectable by immunoprecipitation of the lysosome. Furthermore, expression of 292CA or Q39X mutants in cells inhibits neuronal differentiation. Treatment with ibuprofen reverses mutant-mediated inhibitory differentiation as well as the localization in the lysosome. Conclusions: These results not only explain the cell pathological mechanisms inhibiting phenotype differentiation in cells expressing HLD3-associated mutants but also identify the first chemical that restores such cells in vitro.